Fuzzy Control: - Ying T Wang; R-H Wong; C-W Yu; W-C Huang (Measurement + Control, 2009)
Pneumatic muscle actuators are newly developed actuators in rotational, non-aligned and specified applications. In this paper, pneumatic muscle actuators are used to set up a two-dimensional pneumatic arm to simulate the excavator's motion. Fuzzy control algorithms are typically applied in pneumatic control systems owing to their non-linearity and ill-defined mathematical models. Two fuzzy controllers, which include the sliding mode fuzzy controller and self-organizing fuzzy controller, are comparatively implemented in this 2D pneumatic arm control system. The present paper provides the comparisons of trajectory tracking performances and adaptations of these two fuzzy controllers via a variety of trajectory tracking experiments.